School failure (Portuguese Journal of Family Medicine and General Practice, 2009)
Academic underachievement is a frequent problem in childhood and adolescence and remains a risk factor for underachievement at the personal and professional level and can result in social exclusion. Different personal factors have been implicated with learning difficulties, including systemic diseases and developmental, emotional and behavioural disorders. Early identification of these risk factors is important for successful treatment and so is the modulation of environmental factors. This article will review the various developmental disabilities that can cause learning difficulties and their clinical manifestations. Alternative therapies and their inefficacy will also be discussed.
Keywords: Academic Underachievement; Developmental Disabilities; Dyslexia